2018
DOI: 10.1002/hipo.22846
|View full text |Cite
|
Sign up to set email alerts
|

Time‐varying synchronous cell ensembles during consummatory periods correlate with variable numbers of place cell spikes

Abstract: Spike rates of a hippocampal place cell are not constant and vary even when an animal visits an identical place field with nearly identical behavior. As one potential neurophysiological source underlying place cell spiking variability, we focused on the temporally fluctuating activity states of neuronal ensembles. Spike patterns of hippocampal neurons were recorded from rats performing a linear track task. Within a single consummatory period, similar sets of neurons were more frequently recruited in synchronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A number of studies have shown that hippocampal cell firing within their place fields (termed in-field firing) highly differs when animals pass through an identical space. For example, hippocampal cells specifically increase their in-field firing rates during running toward a given direction, but not in the opposite direction, along a linear path such as a linear track, a W-shaped track, or a radial maze (McNaughton et al, 1983;Frank et al, 2000;Jackson and Redish, 2007;Yagi et al, 2018). Similar directional firing patterns have been found in hippocampal neurons of bats flying in a three-dimensional open space (Sarel et al, 2017).…”
Section: Introductionmentioning
confidence: 59%
“…A number of studies have shown that hippocampal cell firing within their place fields (termed in-field firing) highly differs when animals pass through an identical space. For example, hippocampal cells specifically increase their in-field firing rates during running toward a given direction, but not in the opposite direction, along a linear path such as a linear track, a W-shaped track, or a radial maze (McNaughton et al, 1983;Frank et al, 2000;Jackson and Redish, 2007;Yagi et al, 2018). Similar directional firing patterns have been found in hippocampal neurons of bats flying in a three-dimensional open space (Sarel et al, 2017).…”
Section: Introductionmentioning
confidence: 59%
“…Surgical Procedures. Five and 12 rats underwent surgery to implant recording electrodes only and a combination of recording and stimulating electrodes, respectively (22,39,40). Briefly, the rats were anesthetized with isoflurane gas (0.5 to 2.5%) and an electrode assembly consisting of 16 independently movable tetrodes was stereotaxically implanted above the right hippocampus (3.8-mm posterior and 2.8-mm lateral to bregma).…”
Section: Methodsmentioning
confidence: 99%
“…1,2) Recently, this recording method has been greatly improved owing to the use of 3D printers, enabling us to deal with tens of electrodes in the brain of a freely moving animal. [3][4][5] The amplitude of LFP signals fluctuates at a range of approximately 1 mV, and the sampling rate of LFP signals is 10 kHz or greater. In the peripheral system, major electrical biosignals observed at the peripheral organs include heartbeat signals recorded as electrocardiograms (ECGs) and skeletal muscle signals recorded as electromyograms (EMGs).…”
Section: Methods For Simultaneous Recording Of Bioelectrical Signals From Systemic Or-gansmentioning
confidence: 99%
“…Further details of surgical procedures and recording principles are described elsewhere. 3,9,10) Figure 1B shows representative recorded signals and the corresponding information extracted from those signals. In brain LFP traces, power spectra with frequency bands from 0-100 Hz were constructed by wavelet analysis.…”
Section: Methods For Simultaneous Recording Of Bioelectrical Signals From Systemic Or-gansmentioning
confidence: 99%